Hollow Sn–Ni nanoparticles coated with ion-conductive polyethylene oxide as anodes for lithium ion batteries with superior cycling stability. Issue 51 (5th June 2015) - Zhu, Jin; Jiang, Anni; Shi, Yongqian; Fan, Xin; Dou, Peng; Ma, Daqian; Xu, Xinhua
<x xml:space="preserve">Abstract</x> A facile strategy is designed for the fabrication of hollow, Sn–Ni nanoparticles (NPs) surrounded by ion-conductive, polyethylene oxide (PEO) coating to address the structural and interfacial stability concerns facing Sn-based anodes.